Are Livestock Keepers in and Around Forests Key Stakeholders in Forest Management? Experiences from Mabira Central Forest Reserve, Uganda - Nampanzira, Dorothy K.; Katongole, Constantine B.; Muwanka, Vincent B.; Tabuti, John R. S. (Springer, Cham., 2019)
Globally, forests play an important role in supporting livelihoods of local communities that surround them. However, livestock rearing is hardly considered an important livelihood activity supported by forests. Forests can be a source of pastures which are key feed resources for livestock especially ruminants. There is little information on how a forest reserve affects livestock production especially in sedentary systems. In the current study, the status of livestock production in and around Mabira forest reserve, Uganda, was studied, to characterize the livestock production systems and determine the level of reliance on the forest for forages. A cross-sectional survey was conducted using a structured questionnaire, and a total of 80 households were interviewed. Results revealed that over 70% of the respondent farms had more than one livestock type. Cattle (71%), pigs (49%), chickens (47%) and goats (40%) were the most frequently kept livestock types. Most respondents fed cattle (54%) and pigs (81%) under the stall-feeding system, while 68% of the farms tethered goats. Chickens are mainly fed under free ranging feeding system (66%). Firewood, water, poles for construction and forages were the four forest products of significance importance to households rearing livestock around Mabira forest. Among the key determinants of level of reliance on forages from Mabira forest was negatively and significam, household’s distance to Mabira forest (P <0.01), household size (P <0.05) and landholding size owned by the household (P <0.05) were the variables found to be statistically significant. In conclusion, livestock farmers in and around Mabira forest rear a diversity of livestock types. Forest forages contribute substantially to the feed resource base of a significant proportion of
Keywords: Livestock production; Forage resource; Forest communities; Co-benefits